Incidence and patient survival of myeloproliferative neoplasms and myelodysplastic/myeloproliferative neoplasms in the United States, 2001–12. (7th April 2016) - Srour, Samer A.; Devesa, Susan S.; Morton, Lindsay M.; Check, David P.; Curtis, Rochelle E.; Linet, Martha S.; Dores, Graça M.
Abstract : Descriptive epidemiological information on myeloproliferative neoplasms (MPNs) and myelodysplastic (MDS)/MPNs is largely derived from single institution and European population‐based studies. Data obtained following adoption of the World Health Organization classification of haematopoietic neoplasms and JAK2 V617F mutation testing are sparse. Using population‐based data, we comprehensively assessed subtype‐specific MPN and MDS/MPN incidence rates (IRs), IR ratios (IRRs) and relative survival (RS) in the United States (2001–12). IRs were highest for polycythaemia vera (PV) (IR = 10·9) and essential thrombocythaemia (ET) (IR = 9·6). Except for ET and mastocytosis, overall IRs were significantly higher among males (IRRs = 1·4–2·3). All evaluable MPNs were associated with lower IRs among Hispanic whites than non‐Hispanic whites (NHWs), with the exception of BCR‐ABL1 ‐positive chronic myeloid leukaemia (CML), chronic eosinophilic leukaemia (CEL) and juvenile myelomonocytic leukaemia. Except for CEL, Asians/Pacific Islanders had significantly lower MPN IRs than NHWs. ET, MPN‐unclassifiable and CEL IRs were 18%, 19% and 60% higher, respectively, among blacks than NHWs. Five‐year RS was more favourable for younger (<60 years) than older individuals and for women compared with men, except for PV at older ages. RS was highest (>90%) for younger PV and ET patients and lowest (<20%) for older chronic myelomonocytic leukaemia and atypical BCR‐ABL1 ‐negative CML patients. Varying MPN and MDS/MPN incidence patterns by subtype support distinct aetiologies and/or susceptible populations. Decreased survival rates as compared to that expected in the general population were associated with every MPN subtype, highlighting the need for new treatments, particularly among older individuals.